Training for the future : Jobstarter - objectives, tasks and achievements - Asmuth, Simone [Herausgeber]; Engel, Ute [Herausgeber]; Markus, Anne [Herausgeber]; Gerard, Virginia [Herausgeber]; Kanschat, Katharina [Herausgeber]; Meiborg, Sigrid [Herausgeber] (My University, 2013)
The Federal Ministry of Education and Research (BMBF) has been using JOBSTARTER to generate structural impetuses for vocational education and training all over Germany since 2006. Until July 2013, more than 280 innovative projects have already been supported nationwide via five rounds of funding. All of these projects are delivering tangible results by creating and filling training places in small and medium-sized companies (SMEs) in particular. This brochure provides an overview of the JOBSTARTER programme. (BIBB-Doku)
Keywords: S 2.3.2 Programme in der Berufsbildung; JOBSTARTER; Programm; Ausbildungsplatzförderung